2007
DOI: 10.1016/j.jpainsymman.2006.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Symptoms with Health Outcomes in Chronically Ill Adults

Abstract: Persons with chronic disease experience multiple symptoms. Understanding the association between these symptoms and health outcomes would facilitate a targeted approach to symptom assessment and treatment. Our objectives were to determine the association of a range of symptoms with quality of life, self-rated health, and functional status among chronically ill adults and to assess methods for evaluating the independent associations of symptoms that may be inter-related. We consecutively enrolled 226 cognitivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 34 publications
2
55
1
4
Order By: Relevance
“…Although the correlation coefficient between dyspnea and fatigue was only .41 in this study, other studies have reported a strong relationship between the two sensations, with some patients not being able to distinguish between the two symptoms (Janson-Bjerkelie, KohlmanCarrieri, & Hudes, 1986;Kapella, Larson, Patel, Covey, & Berry, 2006). Interestingly, a recent study of symptom clusters in patients with advanced chronic diseases showed that worse dyspnea was associated with poor health ratings even after adjusting for the effects of six other symptoms including fatigue (Walke, Byers, Gallo, Endrass, & Fried, 2007). This sample was different from ours since it was comprised of patients who had advanced COPD, congestive heart failure, and cancer, therefore, they were living with a very high symptom burden and requiring assistance with their instrumental activities of daily living.…”
Section: Discussioncontrasting
confidence: 51%
“…Although the correlation coefficient between dyspnea and fatigue was only .41 in this study, other studies have reported a strong relationship between the two sensations, with some patients not being able to distinguish between the two symptoms (Janson-Bjerkelie, KohlmanCarrieri, & Hudes, 1986;Kapella, Larson, Patel, Covey, & Berry, 2006). Interestingly, a recent study of symptom clusters in patients with advanced chronic diseases showed that worse dyspnea was associated with poor health ratings even after adjusting for the effects of six other symptoms including fatigue (Walke, Byers, Gallo, Endrass, & Fried, 2007). This sample was different from ours since it was comprised of patients who had advanced COPD, congestive heart failure, and cancer, therefore, they were living with a very high symptom burden and requiring assistance with their instrumental activities of daily living.…”
Section: Discussioncontrasting
confidence: 51%
“…More than 130 relevant articles and abstracts were identified, of which thirty-nine were primary studies published as complete peer-reviewed papers, representing 25 different institutions. Of the thirty-nine papers, thirteen were from Canada 6,11,[20][21][22][23][24][25][26][27][28][29][30] ; eight were from the United States [12][13][14]18,[31][32][33][34] ; eight were from Scandinavia (Sweden 15,[35][36][37] , Denmark [38][39] , Norway 40 , Finland 16 ); two were from Western Europe (Netherlands 41 , United Kingdom 42 ); five were from southern Europe (Switzerland 43 , Italy 17,[44][45][46] ); two were from Australia 47,48 ; and one was from Asia 49 .…”
Section: Methodsmentioning
confidence: 99%
“…The remaining six papers included other populations (patients with AIDS 13 , renal disease 24 , benign disease 29 , and cardiorespiratory diseases 18,22,34 ). Sample sizes in the thirty-three oncologic studies ranged from 32 to 1296 subjects, for a total in excess of 5000 patients.…”
Section: Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a worsening of SRH among 625 participants with HF predicted the onset of the disease 25. In another study, breathlessness or shortness of breath was shown to be associated with poorer SRH 26. As breathlessness is a major symptom of HF, these findings suggest the importance of examining SRH together with other predictors.…”
Section: Discussionmentioning
confidence: 96%